Associação entre atividade física no horário escolar e competência motora de Pré-escolares com e sem aulas de Educação Fisica - Silva, Rennê Honório da (2019)
INTRODUCTION: Different studies corroborate the understanding that children with greater motor competence (MC) present higher levels of physical activity (PA). Considering that structured activities, such as Physical Education (PE) classes can be determinant for increasing levels of PA and as a means of enhancing MC improvement, the objective of this study was to analyze the possible associations between levels of physical activity school hours and the motor competence of a representative sample of preschoolers from the city of João Pessoa with and without Physical Education classes. METHODS: This is a quantitative research with a descriptive, correlational and cross-sectional character. The sample consisted of 201 children of both sexes (99 boys), aged between three and five years (4.51 ± 0.79), enrolled in the Centers of Reference in Infant Education (CREIs) of the city of João Pessoa-PB (Brazil). The PA was evaluated through accelerometry and MC through the Test of Gross Motor Development-2 (TGMD-2, ULRICH, 2000). Descriptive analyzes were performed and the association between the study variables was analyzed using the generalized linear regression model, through the Statistical Package for Social Sciences (SPSS) software version 25.0. A significance level of 5% was adopted. RESULTS: Three separate regression models examined the effects of total physical activity (TPA) on school time, age, and sex on motor scores (total score of MC, locomotion and object control). There were no associations between TPA at school time and the total score of MC, locomotion and control of objects for both groups evaluated (with classes and without EF classes). Age was positively associated with total score, locomotion and control of subjects, either for the group with EF classes (β = 7.75, β = 4.82, β = 3.14), or for the group without classes (β = 7.96, β = 4.13; β = 3.63). Sex presented positive associations only for the group with classes (β = 6.77, β = 2.92, β = 3.85). CONCLUSION: It was observed that TPA during school hours was not associated with MC, nor with the subtests of locomotion and control of objects in both groups (with and without EF classes). Age was presented as a correlate of the total CM and the subtests of locomotion and control of objects for both groups and sex as correlate for the same variables, only for the group with EF classes.